Banking on Borealism. Eating, Smelling, and Performing the North - Schram, Kristinn (Presses de l'Université du Québec, 2011)
This article examines the exotic performances and representations of Icelanders and “the North” (or Borealism) in media and daily life, focusing on food traditions and their practice within intricate foreign–native power relations and transnational folkloric encounters. It suggests a theory for understanding the dynamics, agency, and ironies involved in images of “the North” and the performance of identity amongst “foreigners.” The study looks at Icelandic expatriates and draws examples from media, bankers’ marketing events during the peak of Icelandic business ventures, and the everyday practice of food culture. It explores the roles of identity and folk culture in transcultural performances. In approaching the questions of differentiation and the folklore of dislocation (i.e., among expatriates), the everyday practices of food traditions are studied as an arena of negotiation and performance of identity. Interlinking theory and ethnography, the article examines how expressive culture and performance may corrode the strategies of boundary making and marginalization re- enforced by stereotypes and exoticized representations. Finally, this article looks at the concept of ironic, as opposed to “authentic,” identities.